1996
DOI: 10.1088/0953-8984/8/19/023
|View full text |Cite
|
Sign up to set email alerts
|

A study of substitutional disorder in : I. Fluorescence line narrowing

Abstract: A high-resolution study of the optical properties of Cr 3+ -doped CaYAlO 4 is presented. Excitation into the usual Cr 3+ broad absorption bands produces fluorescence from a very broad R 1 line with a peak at 13 475 cm −1 at 15 K. The R 2 line is observed at an energy 160 cm −1 higher at temperatures above 100 K or by using excitation spectroscopy. The large broadening of the 2 E excited state is attributed to substitutional disorder at the Ca 2+ and Y 3+ sites on the basis of site selective excitation and fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…The spectra for the LiSrAlF 6 and LiSr 0. 8 slightly smaller thermal redshift ͑due to lattice expansion͒ than LiSrAlF 6 , the strong thermal quenching of low energy fluorescence that is observed in gallogermanates and which leads to strong blueshifts 7 is not apparent. Such blueshifts are caused by the preferential nonradiative decay of centers that have stronger electron-phonon coupling.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The spectra for the LiSrAlF 6 and LiSr 0. 8 slightly smaller thermal redshift ͑due to lattice expansion͒ than LiSrAlF 6 , the strong thermal quenching of low energy fluorescence that is observed in gallogermanates and which leads to strong blueshifts 7 is not apparent. Such blueshifts are caused by the preferential nonradiative decay of centers that have stronger electron-phonon coupling.…”
mentioning
confidence: 88%
“…8 It was shown that variation in the Cr 3ϩ environment leads to site-to-site variations in both the crystal field strength and the Huang-Rhys parameter. This results in strong inhomogeneous broadening and fluorescenceexcitation dependences of a particular form.…”
mentioning
confidence: 99%
“…However, the values of B parameter are in their low range [10][11][12][13][14][15]. Using these data the TanabeSugano diagrams [16] for Cr 3+ ion in the studied crystals were drawn (Fig.…”
Section: Article In Pressmentioning
confidence: 99%
“…Yb:CaYAlO 4 has the same structure as Yb: CaGdAlO 4 [13]. In earlier papers [14][15][16][17][18][19][20][21], the properties of Nd, Er, Ti, Ce, V and Tm-doped CaYAlO 4 and Er, Yb co-doped CaYAlO 4 were discussed. CaYAlO 4 crystallizes with the tetragonal K 2 NiF 4 structure.…”
Section: Introductionmentioning
confidence: 99%
“…Between the layers, the divalent Ca and trivalent Y cations reside statistically in ninefold co-ordinated sites, which have distorted C 4v symmetry, and the doped rare earth impurities can substitute in the Ca, Y sites [18]. Besides, the crystal field splittings in CaYAlO 4 are expected to be much larger than in most oxides because the distance d in CaYAlO 4 is small at about 0.19 nm [14]. As a result, multisite replacement and an intense effect from the split crystal field together lead to considerable inhomogeneous broadening of the optical spectra of Yb 3 + in CaYAlO 4 , which permits possible generation of femtosecond (fs) pulses.…”
Section: Introductionmentioning
confidence: 99%